Some Immunologic Evaluations of Toxoplasmosis in Iraqi Aborted Females - Baghdad Science Journal (مجلة بغداد للعلوم, 2007)
Forty-eight aborted women (Iraqi Arab Muslims) at the first trimester with a serological evidence of toxoplasmosis were investigated. Two age- and ethnic-matched control groups were included: 40 aborted women due to accidental events (Control I), and 40 unmarried (virgin) women (Control II). The subjects were evaluated for the following parameters: HLA-class I antigens (A, B and Cw), blood groups, total and differential counts of leukocytes, lymphocyte subpopulations (CD3+, CD4+ and CD20+ cells), phagocytosis of heat-killed yeast (phagocytic index and NBT index), and total serum levels of immunoglobulins (IgA, IgG and IgM) and complement components (C3 and C4). The HLA-A2 and -Cw8 antigens were significantly increased in the patients, while A3 antigen was significantly decreased. Blood group phenotypes in patients and controls also showed significant variations. The total and differential counts of leukocytes showed no significant differences between patients and controls, with the exception of lymphocytes, which showed a significant decreased count in the patients compared to control II. However, the lymphocyte subpopulations showed a significant increased percentage in patients. The phagocytic index was approximated in patients and controls, while NBT index was significantly decreased. Total serum level of IgG was significantly increased in the patients, while IgA, IgM, C3 and C4 levels did not maintain such variation.